Fauna ameaçada de extinção e unidades de conservação na mata atlântica do norte - SILVA, Rafael Leandro Vicente Ferreira da (Universidade Federal do Rio Grande do Norte, 2023)
The Brazilian Atlantic Forest suffers from the loss of area, which causes a decline in biodiversity. Several endemic species inhabit this biome, being considered an important biodiversity hotspot. Many threats surround this forest and have managed to endanger the region's species, many of which are endangered. One of the concrete ways to protect endangered species is through the creation of conservation units, widely applied by the Brazilian government as a conservation strategy. In the Northeast, an area shared by the states of Alagoas, Pernambuco, Paraíba and Rio Grande do Norte is known as the North Atlantic Forest (NAF). The present study analyzed the records of endangered and endangered animal species and their presence or not in the North Atlantic Forest Conservation Units. In this region, the sustainable use UCs are more abundant and occupy a larger area than the full protection UCs within the federal and state spheres. We observed that of the 33 endangered species, only three of them were not registered within the 103 conservation units in the area. We observed more records of critically endangered species outside conservation units that were waiting for it at random (x2 =13.636, p <0.05). There are still endangered species in the region that have not been observed in conservation units. NAF needs more UCs to be able to protect all of its endangered fauna. A Mata Atlântica brasileira sofre com a perda de área, o que ocasiona um declínio de biodiversidade. Nesse bioma habitam diversas espécies endêmicas, sendo considerado um importante hotspot de biodiversidade. Muitas ameaças cercam essa floresta e afetam as espécies da região, das quais muitas são ameaçadas de extinção. Uma das formas concretas de proteger espécies ameaçadas é através da criação de unidades de conservação (UCs), amplamente aplicadas pelo governo brasileiro como uma estratégia de conservação. No Nordeste, a área compartilhada pelos estados de Alagoas, Pernambuco, Paraíba e Rio Grande do Norte é conhecida como Mata Atlântica do Norte ...